TYPES OF SLANG WORDS IN HAUNTED HOTEL CARTOON IN EPISODES 1 - Chintia Handayani; Meriska Yosiana (Universitas Gunadarma, 2026)
Slang represents a dynamic form of informal language that reflects social identity, interpersonal relationships, and cultural practices within speech communities. Although numerous studies have investigated slang in films, songs, and animated media, relatively few have applied Eric Partridge's sociolinguistic taxonomy to contemporary audiovisual discourse. This study aims to identify and analyze the types of slang used in Haunted Hotel Episode 1 based on Eric Partridge's classification of slang. The research employed a descriptive qualitative method using document analysis. The data consisted of slang expressions identified from the official English subtitles and spoken dialogues of Haunted Hotel Episode 1. The data were collected through repeated viewing, transcription verification, identification of candidate slang expressions, and classification according to Partridge's taxonomy. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, including data collection, condensation, display, and conclusion drawing. The findings reveal 15 slang expressions that satisfy Partridge's criteria. All identified expressions belong to Society Slang, including heads up, goddamn it, dude, hell yeah, big bro, jeez, son of a bitch, sis, buddy, what the hell, what the hell is it?, come on man, bitch and damn it. These expressions primarily function to express familiarity, emotional intensity, humor, solidarity, and spontaneity in everyday interaction among family members, hotel staff, guests, and supernatural characters. The dominance of Society Slang indicates that the series emphasizes natural conversational language characteristics of contemporary informal communication. The study contributes to sociolinguistic research by demonstrating the continuing relevance of Partridge's taxonomy for analyzing slang in modern animated television discourse while distinguishing genuine slang from ordinary informal vocabulary and contractions.